Pengaruh Earning Per Share (EPS), Debt To Equity Ratio (DER), Tingkat Inflasi Dan Tingkat Suku Bunga Terhadap Return Saham (Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia di BEI Tahun 2014-2015) - Mariza Aprilia Ariesta; Ronny Malavia (UNIVERSITAS ISLAM MALANG, 2017)
The purpose of this study was to determine the effect of variable Earning Per Share (EPS), Debt to Equity Ratio (DER), Interest Rate and Inflation on Stock Return partially. The population used in this study is a manufacturing base and chemical industry sectors listed on the Stock Exchange during the period 20142015 totaling 66 companies. As many as 66 samples were used mainly companies which meet the requirements of as many as 23 companies. Mechanical sampling using purposive sampling, data analysis methods used in this research is multiple linear regression analysis. The results of this study provide empirical evidence that the variability Earning Per Share (EPS), Debt to Equity Ratio (DER), and the inflation rate has no significant effect on stock returns. While the rate of interest has a significant effect on stock returns.